Effects of hydrogen during annealing process of graphene synthesis via chemical vapor deposition - Ramlan, Amir Hakimi; Sirat, Mohd Shukri; Ismail, Edhuan; Buys, Yose Fachmi; Purwanto, Hadi; Mohd Mustafah, Yasir; Md Din, Muhammad Faiz; Ani, Mohd Hanafi (Science Direct, 2019)
Since the discovery of graphene, chemical vapor deposition (CVD) is by far the best method to produce the material. However, optimization of the process’ parameters is not yet completed. One of the most debatable issues in CVD is the effects of hydrogen towards graphene. In this research, the quality of graphene on copper and palladium substrates as a function of various hydrogen concentrations during annealing as well as different annealing times is studied. Copper and palladium substrates are chosen due to their difference in carbon/hydrogen diffusivity and solubility. Raman analysis showed that upon annealing under higher hydrogen concentration, the graphene grown is defective and with multiple layers. On the other hand, prolonged annealing time is detrimental to the quality of both substrates. Empirical-based calculations showed that both substrates experienced an increase in graphene layers as both H2 concentration and annealing time were increased. We postulate that the presence of defects and multilayer graphene are caused by the hydrogen trapping phenomenon inside the substrates’ vacancies and also the activation of potential defects’ sites through hydrogen adsorption. Graphical representations of the relationship between hydrogen concentration and annealing time towards graphene quality were plotted to suggest the optimized parameters in producing pristine graphene.